2002
DOI: 10.1203/00006450-200210000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Development of Coagulation Regulatory Proteins in the Fetal and Neonatal Lamb

Abstract: To investigate the development of coagulation regulatory proteins-protein C (PC), protein S (PS), and antithrombin (AT)-in relationship to the procoagulant protein factor X (FX), a chronically catheterized fetal ovine model was used. Infusion and sampling catheters were placed into pregnant ewes and their fetuses and maintained from mid-gestation. From a total of 110 fetuses, 17 lambs, and 63 ewes that were studied on one to 15 occasions, 212 fetal, 88 neonatal, and 157 maternal samples were obtained. Liver ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
0
5
0
2
Order By: Relevance
“…Examination of hemostatic function in sheep is primarily important with respect to their role as an animal model of various human diseases and procedures, including surgical methods, 9 surgical trauma, 10–12 cardiovascular surgery, 13–15 sepsis, 16 and shock 17 . However, only a few studies have been published regarding the methods used to investigate primary hemostasis in ovine blood, 18–23 and only one of these utilizes whole blood aggregometry 23 …”
Section: Introductionmentioning
confidence: 99%
“…Examination of hemostatic function in sheep is primarily important with respect to their role as an animal model of various human diseases and procedures, including surgical methods, 9 surgical trauma, 10–12 cardiovascular surgery, 13–15 sepsis, 16 and shock 17 . However, only a few studies have been published regarding the methods used to investigate primary hemostasis in ovine blood, 18–23 and only one of these utilizes whole blood aggregometry 23 …”
Section: Introductionmentioning
confidence: 99%
“…We essentially used TargetScan [17] (release 5.1: http://www.targetscan.org), which provides the prediction results computed by the TargetScanS algorithm, PicTar ( http://www.pictar.mdc-berlin.de) [18], and miRanda ( http://www.microrna.org/microrna/home.do) [19]. …”
Section: Methodsmentioning
confidence: 99%
“…The intrauterine development of PC was explored in ovine models and reported in 1995 by Manco-Johnson et al, 16 who continued to study the fetal development of coagulation regulatory proteins during the subsequent decade. 17 These workers demonstrated that vitamin K-dependent coagulation proteins are characterized by early appearance in plasma despite their delayed fetal maturation. By mid-gestation, factors II, IX, X, PC, and protein S are at 10 to 20% of adult levels whereas factor VII is slightly higher.…”
Section: Introduction: the History Of Developmental Hemostasismentioning
confidence: 99%